+0  
 
0
88
4
avatar+74 

Expand \(-(3-c)(c+2(3-c))\).What is the sum of the coefficients of the expanded form?

 Jun 9, 2021
 #1
avatar+11835 
+2

-(3-c)(c+2(3-c))

 

Hello Guest!

 

- (3 - c)(c + 2(3 - c)) = - (3 - c)(c + 6 - 2c)

= - (3c + 18 - 6c - c² - 6c + 2c²)

= - c² + 9c -18

Which coefficients do you mean?

laugh  !

 Jun 9, 2021
 #2
avatar+74 
0

all of them so -1,9, and. -18 right?

Wsai12  Jun 9, 2021
edited by Wsai12  Jun 9, 2021
 #3
avatar+2106 
+2

I think it's -1, 9, -18. 

Another cool trick you can use to find the sum of coefficients is to just plug in c as 1. 

-(3-1)(1+2(3-1))

This works because the final answer in expanded form will look like xc^2 + yc + z, and if c = 1, x1^2 + y1 + z = x + y + z, which is the sum of the coefficients. :))

 

=^._.^=

catmg  Jun 9, 2021
 #4
avatar+713 
+1

Thats a very nice trick, catmg!

MathProblemSolver101  Jun 10, 2021

15 Online Users

avatar
avatar